Cumulative incidence of entry into out-of-home care: Changes over time in Denmark and England. (April 2015) - Ubbesen, Mads-Bonde; Gilbert, Ruth; Thoburn, June
Abstract: Policies and thresholds vary for placing children into out-of-home care (OHC) at different ages. Evidence is lacking that quantifies the risk of entering OHC by age, and how this varies over time and between countries. We determined the age-specific cumulative incidence of ever entering OHC during childhood in Denmark and in eight local authorities in England. We used administrative data for any form of OHC (except respite care) provided by children's social services in Denmark and England from 1992 to 2008. Using life tables and national population estimates, we calculated the cumulative incidence of entry into OHC by year of age for cohorts born in 1992–1994 through to 2006–2008. The cumulative incidence of entry into OHC decreased over time in Denmark and increased in England at all ages. Cumulative incidence of OHC in the first year of life was similar in Denmark and England for infants born in 1992–1994 (Denmark 2.83/1, 000, England 2.89/1, 000), but infants born in 2007–2008 were nearly three times as likely to enter OHC before their first birthday in England (4.50/1, 000) than in Denmark (1.61/1, 000). Entry into OHC during adolescence was more common in Denmark than in England so that by 16 years old the cumulative incidence of ever entering OHC during childhood was twice as high in Denmark (33.83/1, 000) as in England (15.62/1, 000). Diverging trends over time in the use of OHC in Denmark and England are likely to reflect changing policies in the two countries.